Cardiovascular and relative exertion perceived response during proprioceptive neuromuscular facilitation exercise associated to pulley. - Silva, Alessandra Araujo da; Lobato, Arianne Nunes; Pereira, Elder Nascimento; Silva, Flávio Socorro da; Junior, Renato Campos Freire; Arêas, Fernando Zanela da Silva; Arêas, Guilherme Peixoto Tinoco (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The use of pulley together with proprioceptive neuromuscular facilitation (PNF) are described how an excellent approach for several exercises, but prescribe with safety is very difficult and it’s a failure in the rehabilitation area, yet. Objective: To measure the hemodynamic changes and the relative exertion perceived through OMNI - RES scale after use PNF exercise together pulley. Method: 10 healthy sedentary women performed the exercises with right upper body together with PNF and pulley load. It was performed 3 sets with 10 repetitions and measurement blood pressure, heart rate and perceived exertion among the three series. ANOVA post hoc Bonferroni, accepting p<0.05. Results: One subject dropped out due to lack of exercise program adherence. In the hemodynamic’s data was observed significance differences in HR (1st, 2nd and 3rd in relationship at rest, p < 0.05), PE (1st, 2nd and 3rd in relationship at rest, p < 0.05). In the perceived exertion was difference among 3rd set in relationship for 1st set (p > 0.05). Conclusion: The use of exercises with the PNF patterns associated with pulleys do not produce great cardiovascular influences, be safe in healthy individuals.